Robustness Evaluation of Elastoplastic Base-Isolated High-Rise Buildings Subjected to Critical Double Impulse - Fujita, Kohei; Yasuda, Keisuke; Kanno, Yoshihiro; Takewaki, Izuru (Frontiers in Built Environment, 2017)
A new method of robustness evaluation is proposed for an elastoplastic base-isolated high-rise building considering simultaneous uncertainties of structural parameters. Since it is difficult to evaluate the robustness of elastoplastic structures due to heavy computational load on the time-history response analysis including elastoplastic response, a double impulse input is used to provide a closed-form solution of the critical response of a single-degree-of-freedom (SDOF) elastic-perfectly plastic structure under a near-field ground motion. Introducing an equivalent elastoplastic SDOF model of a base-isolated high-rise building, the worst combination of uncertain structural parameters, i.e. the stiffness and yield deformation at the base-isolation story and the stiffness of the superstructure, can be derived which leads to the upper bound of the critical elastoplastic response. It is shown that, by using the derived upper bound of the critical response, the robustness function, a measure of the robustness, of elastoplastic structures can be evaluated efficiently. In numerical examples, the robustness of a 30-story base-isolated high-rise building is compared with those of other models with different yield deformations at the base-isolation story to find a preferable design with larger robustness.